THE LEVEL OF ENVIRONMENTAL SENSITIVENESS OF PURSE SEINE FIRING AT KM SAMOSIR 08 AND KM SERASI PUTRA IN THE CITY OF SIBOLGA, NORTH SUMATERA - Hutapea, Roma Yuli; Haris, Rangga Bayu Kusuma; Hasibuan, Sony Cristian; Ikhsan, Suci Asrina; Pramesthy, Tyas Dita; Arkham, Muhammad Nur (Aurelia Journal, 2023)
There are several types of purse seine in Sibolga, namely tuna trawls, snare seines and meeting trawls. The main catch from purse seine is pelagic fish. Purse seine catches are related to the mesh size of the fishing gear. The mesh size is small so it can catch more than 3 species of catch which are classified as non-environmentally friendly fishing gear. The aim of this research is to find out whether purse seine fishing gear in Sibolga is environmentally friendly fishing gear or not. The research was conducted March 1 – June 30 2021 at the Sibolga Fishing Port (PPN), The research was carried out at KM Samosir 08 on cob trawl fishing gear and KM Serasi Putra on cob trawl fishing gear. The data analysis used is a scoring analysis of environmentally friendly fishing gear criteria. Trawls and cob trawls are environmentally friendly fishing gear and meet the 9 criteria for environmentally friendly fishing gear. The score for the level of environmental friendliness of the tuna trawl fishing gear was 33 and the meeting trawl was 32.6 with the criteria being included in the group of very environmentally friendly fishing gear.